MODUL PEMBELAJARAN FIQIH BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI MADRASAH TSANAWIYAH AISYIYAH MUHAMMADIYAH PALEMBANG - Nurul Syariah Daulay; Annisa; Ardhia Pramesti R.C; Muhamad Fauzi; Widya Wulandari (STKIP Subang, 2026)
This study aims to determine the implementation of fiqh learning based on local wisdom to improve students' learning motivation at MTs Aisyiyah Muhammadiyah Palembang, as well as to identify the obstacles and solutions in its implementation. This study used a qualitative approach with a field research design combined with a literature study. Data were collected through observation, interviews, and documentation, with the fiqh teacher, as the main informant. The data were analyzed descriptively through an in-depth review of interview results and presented in a systematic narrative form. The results showed that local wisdom-based fiqh learning was carried out by connecting fiqh materials with cultural values and traditions that are closely related to students' daily lives. The learning process emphasized not only theory but also practice by utilizing various learning resources and teaching aids, such as prayer procedure posters and a miniature Kaaba. This approach helped students understand the material more easily, become more active in the learning process, and increase their motivation to learn. The obstacles encountered included low learning interest among some students, differences in students' abilities, and limited instructional time. To overcome these obstacles, the teacher modified and combined various teaching methods to create a more engaging and understandable learning environment. In conclusion, the implementation of local wisdom-based fiqh learning was effective in improving students' learning motivation.